Démarches d’ergonomie participative pour réduire les risques de troubles musculo-squelettiques : bilan et réflexions - Marie St-Vincent; Georges Toulouse; Marie Bellemare (Perspectives Interdisciplinaires sur le Travail et la Santé)
This paper discusses the participatory ergonomic interventions of three researchers in different environments. The introduction situates the developed approach in relation to the literature on the subject. An assessment is then presented of the main components of our approach. The major characteristics of the approach are described first, followed by an explanation of the participation structures, including the Ergo groups. The workers’ place in the company is discussed and aspects of the training are presented. The actions carried out with regard to the work situations are detailed, from the selection of hazardous workstations, to solution implementation and follow-up. A table presents the characteristics of the environments studied and summarizes the interventions carried out on 38 work situations. The changes often involve workstation layout, equipment and tools, and more rarely, work organization. The discussion focuses on sharing reflections based on our practices and on identifying research scenarios. Five topics are discussed : the impact of the organizational and social context on the participatory approach ; the processes in play within the Ergo groups ; the quality of the participants’ analyses ; the place of organizational and psychosocial factors in the participatory approach ; and the issues related to the evaluation of this approach. The conclusion presents the strong points and limitations of the approach and proposes some avenues for future research.